Application of The Student Teams Achievement Division Method in a Cooperative Learning Approach to Learning Islamic Education at SMP Muhammadiyah 4 Giri - Indri Wulan Ramadhani P; Noor Amirudin (Ar-Fachruddin: Pendidikan Agama Islam, 2024)
This research aims to explore the application of the Student Teams Achievement Division (STAD) method within a cooperative learning approach to Islamic Education (PAI) at SMP Muhammadiyah 4 Giri. Conducted during the Odd/Even semester of the 2023/2024 academic year, this classroom action research utilizes a descriptive qualitative paradigm. The subjects of the study are students from SMP Muhammadiyah 4 Giri. Data collection techniques include observation sheets, test results, and documentation, while data analysis involves data reduction, data presentation, and drawing conclusions. The results indicate that the STAD method effectively enhances student engagement and learning outcomes in Islamic Education by fostering collaboration and active participation among students. The study concludes that the cooperative learning approach, particularly the STAD method, significantly contributes to improving students' academic achievements and interest in Islamic Education